A super-twisting observer for atomic-force reconstruction in a probe microscope. (January 2020) - Zhang, Kaiqiang; Hatano, Toshiaki; Nguyen, Thang Tien; Edwards, Christopher; Herrmann, Guido; Burgess, Stuart; Antognozzi, Massimo; Khan, Said; Harniman, Robert; Miles, Mervyn
Abstract: This paper presents a new methodology, employing a super-twisting sliding mode observer, to reconstruct un-measureable atomic-forces at nano-Newton precision in a Vertically Oriented Probe Microscope (VOPM). The VOPM senses the deflection of a vertically oriented cantilever, caused by shear-force interaction with a confined water layer above the sample-substrate. The paper describes the development of a model and the subsequent experimental process for computing its parameters. This forms the basis for the design of a super-twisting observer to estimate the unknown shear-forces. The reconstructed force can be decomposed into elastic and viscous components, which are important in biological research.